Prevalence of positive PCR assay for neisseria gonorrhoeae and chlamydia trachomatis among asymptomatic thai males attending STD clinic at thailand's tertiary referral center - S. Jiamton (2020)
© 2019, Medical Association of Thailand. All rights reserved. Background: Asymptomatic Chlamydia trachomatis (CT) and Neisseria gonorrhoeae (GC) infections continue to be a global public health concern. Objective: To investigate the prevalence of, and the factors associated with positive urine polymerase chain reaction (PCR) assay for CT and/or GC infection among asymptomatic patients. Materials and Methods: The present study was a cross-sectional study conducted with positive urine polymerase chain reaction (PCR) assay between August 2015 and September 2016. Results: One hundred eight patients were recruited. Mean age was 41.2 years. The overall prevalence of positive urine PCR for CT and/or GC in asymptomatic patients was 9.3%. Eight (7.4%) were positive for CT, three (2.8%) were positive for GC, and one (0.9%) patient tested positive for both organisms. In multivariate analysis, younger than 40 years (adjusted OR 14.5, 95% CI 1.4 to 166.7; p=0.027), education less than bachelor's degree (adjusted OR 6.1, 95% CI 1.0 to 35.7; p=0.045), and unemployment (adjusted OR 18.5, 95% CI 1.3 to 250.0; p=0.034) were found to be independent predictors of positive urine PCR for CT and/ or GC infection. Conclusion: The overall prevalence of positive urine PCR for CT and/or GC infection in asymptomatic patients was 9.3%. Younger than 40 years, education less than bachelor's degree, and unemployed status were found to be independent predictors of CT and/or GC infection.